2008
DOI: 10.1021/pr7007829
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profiling of Breast Tumors by Gel Electrophoresis and Nanoscale Electrospray Ionization Mass Spectrometry

Abstract: We have conducted proteome-wide analysis of fresh surgery specimens derived from breast cancer patients, using an approach that integrates size-based intact protein fractionation, nanoscale liquid separation of peptides, electrospray ion trap mass spectrometry, and bioinformatics. Through this approach, we have acquired a large amount of peptide fragmentation spectra from size-resolved fractions of the proteomes of several breast tumors, tissue peripheral to the tumor, and samples from patients undergoing nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…We also confirmed the increased expression of the PDIA3 gene in IDC compared with normal breast tissue (P < 0.001) by RT-qPCR and found differential expression of both genes in more aggressive tumor subsets, such as in lymph node metastasis and grade III tumors (Ramos et al, 2015). A comparative proteomic study of breast tumors and adjacent normal tissue also showed increased expression of PDIA3 and PDIA6 proteins in breast carcinoma (Alldridge et al, 2008). Pressinotti et al (2009) investigated the differential expression of PDIA3 in prostate cancers.…”
Section: Molecular Chaperones/heat-shock Proteinssupporting
confidence: 71%
“…We also confirmed the increased expression of the PDIA3 gene in IDC compared with normal breast tissue (P < 0.001) by RT-qPCR and found differential expression of both genes in more aggressive tumor subsets, such as in lymph node metastasis and grade III tumors (Ramos et al, 2015). A comparative proteomic study of breast tumors and adjacent normal tissue also showed increased expression of PDIA3 and PDIA6 proteins in breast carcinoma (Alldridge et al, 2008). Pressinotti et al (2009) investigated the differential expression of PDIA3 in prostate cancers.…”
Section: Molecular Chaperones/heat-shock Proteinssupporting
confidence: 71%
“…It has been reported that Nanog expression up-regulates most cancer types such as carcinoma in situ, embryonal carcinomas, and cervical and ovarian cancers (39). Mass spectrophotometric analysis of frozen BC specimens showed that Nanog is one of the most highly increased proteins (40). Oct4, similar to Nanog, is an essential transcription factor for maintaining the stemness of both ESCs and CSCs (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins were extracted from the frozen tumor samples with 2X SDS sample buffer, reduced, alkylated and separated by gel electrophoresis as previously described 5 . The gel lanes were sliced and digested as described previously 5 .…”
Section: Methodsmentioning
confidence: 99%